Angular orientation of the stable tyrosyl radical within photosystem II by high-field 245-GHz electron paramagnetic resonance. - Un, S (1994)
The 4 K 245-GHz/8.7-T electron paramagnetic resonance spectrum of the stable tyrosyl radical in photosystem II, known as TyrD., has been measured. Illumination at 200 K enhances the signal intensity of TyrD. by a factor of > 40 compared to the signal obtained from dark-adapted samples. This signal enhancement and the unusual line shape of the TyrD. resonance result from the magnetic dipolar coupling of the radical to the manganese cluster involved in oxygen evolution. The relative angular orientation of the manganese cluster with respect to TyrD. has been determined from line-shape analysis. The resonance arising from TyrD. in Tris-washed manganese-free photosystem II sample is also distorted. This effect probably originates from the influence of the nonheme iron on the spin relaxation of the tyrosyl radical. The relative angular orientation of the nonheme iron has also been determined. Oriented samples were used to determine the angular orientation of TyrD. with respect to the membrane plane. Combining angular data with published distances, we have constructed a three-dimensional picture of the relative positions of TyrD., the manganese cluster, and the nonheme iron. The data suggest a more symmetrical placement of the manganese relative to TyrD. and TyrZ, the tyrosine involved in electron transfer, than is usually assumed in current models of photosystem II.